Examining educators' views of classroom management and instructional strategies: school-site capacity for supporting students' behavioral needs. Issue 1 (2nd January 2020) - Oakes, Wendy Peia; Cantwell, Emily D.; Lane, Kathleen Lynne; Royer, David J.; Common, Eric Alan
Abstract: Schools are adopting tiered systems to prevent and respond to students' academic, behavioral, and social needs. Foundational to tiered systems is the capacity of educators to implement high-quality classroom management and instructional practices. In this study, school leaders provided professional development to staff as they prepared to adopt a tiered system districtwide. We examined self-assessments of research-based strategies for 61 middle school educators who participated in school-led professional development, a book study. The purpose was to understand educators' current views of their knowledge and skills of practices covered. Results suggested educators reported being more knowledgeable and confident in classroom management practices, followed by instructional strategies, and low-intensity strategies. Participants expressed that the book study supported school goals. Limitations and directions for future inquiry are explored.